Genre Analysis of English vs. Indonesian Application Letters - Warsidi Warsidi; Warsidi (Yayasan Visi Intan Permata, 2022)
Genre studies in English for specific purposes (ESP) have long been widely investigated, including in academic and professional texts. In professional texts, these studies have been conducted in business letters, formal letters, newsletters in China and Australia, advertising promotional media in Indonesia, and application letters. However, application letters are still the least investigated in the Indonesian context. Furthermore, contrastive genre analysis of English and Indonesian application letters has never been investigated to date. Based on finding and comprehending this gap in the literature, the researcher is encouraged and interested in conducting the present study. The researcher involved and trained 12 English foreign language (EFL) students to analyze rhetorical moves of 63 English and 63 Indonesian application letters. However, among the 63 English application letters, 25 were written by non-native English speakers. Thus, the researcher only focused on analyzing 38 English and 63 Indonesian application letters. Then, to ensure the validity of the analysis results, the researcher reanalyzed the rhetorical moves by re-reading application letters three times using a top-down approach and identifying their linguistic signals. The results showed two rhetorical models of English and Indonesian application letters. These two models imply that they have rhetorical differences in communicating their purposes.